G20 Health Vision in Achieving SDGs 2030: Arranging the Global Health Management Architecture - Muhammad Alfarizi; Rafialdo Arifian (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2022)
Background The Covid-19 pandemic is proof that without being healthy, the entire joint sector of the world's development will be destroyed with just one outbreak of a disease. This article is intended to analyze the scientific literature on the issue of structuring global health management in order to re-implement the goals of the World SDGs with a new global health management architecture frame and at the same time create high hopes for the recovery of world conditions after the Covid-19 Pandemic through the G20 Meeting which will be held in Indonesia. Methods This study uses the traditional literature review method with the role of researchers looking for and combining the essence and analyzing facts from scientific sources according to valid and accurate criteria. Results There are six pillars of the global health management architecture that must stand upright including standardized global health protocols, digitization of health services and access justice, local wisdom complementary medicine and strengthening collaboration across countries and across scientific disciplines. Conclusions The establishment of standardized global health protocol standards, efforts to digitize health services from a public health and economic perspective, open access to diagnostic tools, drugs, and vaccines in a fair manner and strengthen innovation of health products based on local wisdom are the pillars of global health management that currently must stand to build a world of peace and prosperity based on the goal of SDGs 3 Health.